Religião e política no campo evangélico contemporâneo : ancoragens, homologias e retraduções - Santos, Gilberto de Moura (2016)
The presence of religious actors in the construction of public debate is, in Brazil, undisguised. Thus, we highlight the evangelical churches. Some denominations are relatively able to mobilize its members around specific demands or to broader political projects. However, religious filiations do not define political memberships. Affinity relationships between the two spheres are usually partial, and very complex. It is true that a faithful engaged in order to justify their political positions, will tend to evoke religious views available in the group to which it belongs. But this fact does not necessarily produce very stable identity convergences in the group, since the religious or political ideas are constantly retranslated by agents. Thus, the homologies raised here and regularities in the actions of individuals are contingent, however, always possible. Occasionally, they translate into modes of participation, inclusion of the faithful in public areas, political memberships and speeches somehow anchored to particular ways to experience religion. So it initially asks: what types of links between religion and politics are being produced in different social areas of interest to this investigation? Such homologies produce significant regularities, identity definitions? To tackle these problems, we used a focused research on participant observation that it intended to collate the political positions undertaken by evangelical believers focused on this work in the face of religious justifications for them mobilized. What entailed an analysis of the different discourses that try to justify the involvement of religious actors in the public debate. The thesis also searched far-reaching convergences in the contemporary evangelical discourse; also why, they were listed in the investigation two very different denominations: the Traditional and the second wave Pentecostals. Despite the diversity found within the studied groups, and the uniqueness of each religious denomination, the survey encountered a type of speech, widespread in varying degrees in religious spaces, it is called here pragmatic conservatism.